Granulocyte-colony stimulating factor-producing gallbladder carcinoma-include analysis all case reports: A case report. (2016) - Izumo, Wataru; Furukawa, Kenji; Katsuragawa, Hideo; Tezuka, Toru; Furukawa, Tatsuya; Hataji, Kenichirou; Komatsu, Akio; Shigematsu, Kyousuke; Yamamoto, Masakazu
Highlights: G-CSF producing gallbladder carcinoma is rare and has a poor prognosis. We report a long term survival of G-CSF producing gallbladder carcinoma. We suggest multidisciplinary therapy prolong the survival of patients with G-CSF producing gallbladder carcinoma. Abstract: Introduction: It is extremely rare for gallbladder carcinoma to produce granulocyte-colony stimulating factor (G-CSF) and such tumors have a poor prognosis. Presentation of case: A 67-year-old man was admitted with continuous fever. Laboratory tests showed a leukocyte count of 27, 980/μL, serum C-reactive protein (CRP) of 9.2 mg/dL and serum G-CSF of 225 pg/mL. Imaging revealed an irregular gallbladder mass about 90 mm in diameter with peripheral enhancement that also involved the liver and transverse colon. G-CSF producing gallbladder carcinoma was diagnosed. We performed cholecystectomy, partial resection of segments 4 and 5 of the liver, partial resection of the transverse colon, and gastrostomy. Histopathological examination showed gallbladder carcinoma (pT3, pN0, M0, G2, and pStage IIIA by the UICC classification, version 7). On immunohistochemical staining, tumor cells were positive for G-CSF. The leukocyte count was normalized postoperatively and fever subsided immediately after surgery. Two months later, the leukocyte count rose to 56, 820/μL and metastases to the liver and lymph nodes were detected by CT. Chemotherapy (gemcitabine plus cisplatin) was started and the leukocyte count was normalized after the first course. The patient has continued chemotherapy and has survived for 16 months postoperatively. Discussion: G-CSF producing gallbladder carcinoma has a poor prognosis and most patients die within 12 months of starting therapy. It is rare for patients with recurrence to survive for 16 months after surgery, as in the present case. Conclusion: Multidisciplinary therapy (surgery and chemotherapy) may prolong the survival of patients with G-CSF producing gallbladder carcinoma, especially those with recurrence.